PELATIHAN APLIKASI KEUANGAN BUKUWARUNG DAN BAHASA INGGRIS MENDUKUNG BISNIS USAHA PADA MASYARAKAT UMKM CIPTA ASRI KOTA BATAM: Training of BukuWarung Accounting Application and English to Support Micro Business Around Cipta Asri Society Batam City - Yulia Yulia; Ance Jusmaya; Diamon Sembiring (ASOSIASI IDEBAHASA KEPRI, 2023)
The transformation from past technology to more advanced technology is easy and fast. In the past, before the age of computers, let alone smartphones, bookkeeping in business was usually done using books, business bookkeeping records usually used legend books, which were quite thick and quite complicated when looking for debt and credit data based on date, because everything was written manually. Now there is a BukuWarung application that can be used for stalls, internet cafes, salons, photocopying businesses, and so on. BukuWarung's financial application is very easy to use and provides many benefits such as data that is stored securely, can make different bookkeeping, remembers automatic debt payments, available cashier application, automatic financial reports, and other benefits. The BukuWarung financial application is very practical, you only need a smartphone and don't carry books anywhere.